SELF-RATING OF THE PROFESSIONAL PURPOSES AND THEIR REALIZATION OF THE WOMEN PERFORMING TRADITIONAL AND NON-TRADITIONAL PROFESSIONAL ROLES - Julia V. Artamoshina (Вестник Северо-Кавказского федерального университета)
Statement of the professional purposes is one of the most important things in the formation of personali- ty and activity. Women who perform traditional and non-traditional professional roles differently estimate their professional purposes and are aimed at different implementation of professional purposes.